EFFICIENCY OF FATTY ACID-FREE DEFINED SYSTEM FOR IN VITRO MATURATION OF BUFFALO OOCYTES - A. Azam; Asma-ul-Husna; Q. Shahzad; T. Akhtar; Ehsan-ul-Haq; N. Ullah; S. Akhter (Journal of Animal and Plant Sciences, 2017)
The evaluation of medium for in vitro maturation of buffalo oocytes has progressed towards more defined conditions for the studies evaluating effect of specific components in the medium. Therefore, aim of the present study was to evaluate the effect of fatty acid free-bovine serum albumin (FAF-BSA) alone or supplemented with epidermal growth factor (EGF) in the in vitro maturation medium on in vitro maturation of oocytes and subsequent embryo development. The cumulus oocyte complexes (COCs) were collected from ovaries (900) of slaughtered animals by aspirating follicles, and incubated in maturation medium for 24 h. Three types of maturation media (MM) supplemented with 1) 10% fetal calf serum (FCS), 2) 6 mg/ml FAF- BSA or 3) 6 mg/ml FAF- BSA + 10.0 ng/mL epidermal growth factor (EGF) were evaluated. After maturation, Tyrode’s albumin lactate pyruvate (TALP) and synthetic oviductal fluid (SOF) media were used for fertilization and culture environments, respectively. The percentage of COCs with expanded cumulus was higher (P < 0.05) in MM supplemented with FBS and FAF-BSA+EGF compared with that having FAF-BSA alone. No difference (P > 0.05) was observed in meiotic resumption and nuclear maturation rate in all three types of maturation media. Percentage of embryos crossing 8-16 cell stage and reaching up to 32 cell stage (morula) after IVC was lower (P < 0.05) in MM supplemented with FAF-BSA, however with addition of EGF, embryo development was improved (statistically non significant) and was comparable (P>0.05) with development in MM supplemented with FCS. In conclusion, serum free defined system having FAF-BSA+EGF was comparable to the MM containing FCS and can be used to replace serum supplemented media for the in vitro maturation of buffalo oocytes and further embryo development.
Keywords: In vitro maturation; serum free medium; defined medium; epidermal growth factor